Psychological Treatments for Hyperactivity and Impulsivity in Children with ADHD: A Narrative Review - Shayan Sadr-Salek; Andreia P. Costa; Georges Steffgen (MDPI AG, 2023)
Treatment of the ADHD types (hyperactive-impulsive, inattentive, and combined) in children has rarely been studied separately, although their prognostic courses differ widely. In addition, data show that improvements in hyperactivity/impulsivity are hard to achieve. Thus, we focused on treatments tailored to hyperactivity/impulsivity. We examined meta-analyses and systematic reviews within the inter- and intra-individual treatments and found that psychoeducation and training for parents, school-based interventions, reinforcement strategies, and neurofeedback consistently showed small to moderate effect sizes in reducing hyperactivity/impulsivity in children. Conversely, emotional self-regulation, social skills, and cognitive trainings showed unsatisfactory results. In summary, we found that the quality of usual care can be surpassed when the designated interventions are purposefully combined into a multimodal treatment program.